KOMPETENSI TENAGA KERJA KONSTRUKSI DALAM MENGHADAPI ERA LIBERALISASI - Bada Haryadi (Universitas Negeri Yogyakarta, 2010)
One factor affecting the quality in the construction section is the qualit of the work force. As we have seen in the last decade, the order of life in general and the order of economic, in particular, is undergoing to shift the paradigm towards global. In one side, the opportunity of cooperativeness among countries become wide open, the competition among countries increasingly tight. The un-competitive countries will be wiped out by those free trade and only the competitive countries will survive. To enhance the ability of competition in the free trade, required capabilites and competitiveness of power of human resources. The ability or the competence of the human resources in the construction services sector, is the only active resources that can determine the stability of the construction process. Construction of labour in conditions more commonly known by the constructors (construction’s craff) is the mostadvanced involved and deal directly with the implementation of a construction site. As a builder of the most advanced labor course must have specialization and competence in specific areas and certified. This is important and needs to be prepared within the framework of the current workforce in the era of liberalization. Given the specialization and certification of construction of Indonesian workers are expected to be accepted and able to compete with foreign construction workers. Besides having the competence and certification of construction workers are expected to not be labeled as low labor who only follow orders from the foreman, but also can take the initiative and be proactive to avoid failures during construction. One way that can be taken so thatworkers have the adequate specialization and competence is to conduct training and certification required by the engineer.Keyword: workforce, competence, certified.